2017
DOI: 10.1097/igc.0000000000000965
|View full text |Cite
|
Sign up to set email alerts
|

C1GALT1 Seems to Promote In Vitro Disease Progression in Ovarian Cancer

Abstract: C1GALT1 modifies O-glycan expression and enhances malignant behaviors in ovarian cancer cells, suggesting that C1GALT1 plays a role in the pathogenesis of ovarian cancer and targeting C1GALT1 could be a promising approach for ovarian cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…We demonstrated that OVCAR3 SC exhibit decreased cell proliferation and increased apoptosis compared to parental OVCAR3 cells. These findings are in agreement with the results by Chou et al [ 36 ], who found that the knockdown of the C1GalT1 enzyme leads to decreased growth of OVCA cells [ 36 ]. Moreover, we found that OVCAR3 SC, despite increased cell migration, also exhibit a reduction in the mesothelial clearance capacity and form smaller and less invasive tumours in the mice model.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that OVCAR3 SC exhibit decreased cell proliferation and increased apoptosis compared to parental OVCAR3 cells. These findings are in agreement with the results by Chou et al [ 36 ], who found that the knockdown of the C1GalT1 enzyme leads to decreased growth of OVCA cells [ 36 ]. Moreover, we found that OVCAR3 SC, despite increased cell migration, also exhibit a reduction in the mesothelial clearance capacity and form smaller and less invasive tumours in the mice model.…”
Section: Discussionsupporting
confidence: 93%
“…Chou et al explored the role of C1GALT1 in ovarian cancer [53]. The elevated expression of C1GALT1 was associated with poor survival in ovarian cancer patients.…”
Section: Core-1 Synthase Behaves Differently In Different Cancersmentioning
confidence: 99%
“…There are still some limitations in this study. Besides HNSCC, C1GALT1 is also overexpressed and plays an important role in hepatocellular carcinoma, breast cancers, ovarian cancers, colorectal cancers, prostate cancers, and esophageal cancers 25–30 . It is possible that patients with cancers other than HNSCC may have elevated anti‐C1GALT1 autoantibodies.…”
Section: Discussionmentioning
confidence: 99%